The use of (GACA)4 PCR to sex Old World vultures (Aves Accipitridae) - Wink, Michael; Sauer-Gürth, Hedwig; Martinez, F.; Doval, G.; Blanco, G.; Hatzofe, O. (Molecular ecology, 1998)
A PCR method was developed employing a single primer (GACA)4 to sex Black vultures (Aegypius monachus), Lappet-faced vultures (Torgos tracheliotus), and Griffon vultures (Gyps fulvus). Using the (GACA)4 primer several PCR products were generated. One or more PCR products displayed a sex-specific pattern, i.e. they were only present in females (probably corresponding to repetitive DNA on the W chromosome) but absent in males. The sex ratio of 85 Griffon vultures from Spain was almost 1.
Elektronische Reproduktion der Druck-Ausgabe 28. Februar 2002
Gesehen am 03.08.2023